Implementasi Metode Penalaran CBR dalam Mengidentifikasi Gejala Awal Penyakit Jantung menggunakan Algoritma Sorensen Coeffient - Vicky Agnes Arundy; Iskandar Fitri; Eri Mardiani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Heart disease is a condition when the heart is experiencing a disorder. The forms of disturbance that are experienced are usually various. Usually there is a disturbance in the blood vessels of the heart, heart rate, heart cover, or congenital problems. The heart itself is a muscle consisting of four chambers. That is, the first two rooms are located at the top, the atrium (foyer) to the left and right. Then the other two rooms are at the bottom, namely the right and left ventricles. To provide information on how to diagnose the type of disease and how to control heart disease, an application of an expert system that can represent someone who is an expert in their field is needed to provide solutions to this disease problem using the Case-Based Reasoning method with the Sorensen Coeffient approach. The result of this research is the creation of an expert system for diagnosing heart disease using the Case-Based Reasoning method with the Sorensen Coeffient approach which is able to provide solutions to heart disease.